Hexagonal patterns in thin films: Experiments and modeling. (March 2015) - Kattouf, Basila; Warwar, Christine; Balla, Itamar; Shasha, Hila; Sherman, Dov; Frey, Gitti L.
Abstract: Perfect periodic hexagonal patterns were obtained in our lab in μ m -thick drying polymer/metal oxide composite films. The appearance of the pattern depends mainly on the polymer and metal oxide ratio, while the size of the features depends on the temperature of deposition. To understand the generation of the hexagonal pattern we filmed the hexagons' nucleation and development in real-time, and suggest a corresponding model. The model shows that the hexagonal pattern initiates at a single point, advances through plastic deformation, and continuously and rapidly propagates to cover the entire surface. We show that this highly symmetrical pattern reduces most efficiently the strain energy in the material. The model correlates the pattern generation conclusively with uniformly- and rapidly-generated local plastic deformation, and not brittle fracture.